Landscape and Work: 'Placing' the Experiences of Male Manual Workers in a UK Seaside Town. (October 2022) - Simpson, Ruth; Morgan, Rachel; Lewis, Patricia; Rumens, Nick
This article explores the experiences of white, male manual workers in Hastings, East Sussex – a mid-sized UK seaside town that has undergone long-term decline in employment opportunities. Informed by the theoretical insights from Bourdieu, it focuses on the role of place in shaping the employment paths of a group that has arguably been 'left behind' by local and global forces. Drawing on broader notions of place as landscape and highlighting the significance of 'immobility and dependence', 'competitive localism and belonging' and 'bounded potential', it examines how landscape conditions are implicated in the meanings given to work experiences, perceived employment opportunities and future aspirations. We argue that incorporating landscape into Bourdieu's Theory of Practice extends our understanding of landscape's influence on employment experiences and its unique capacities as both a physical and a socially constructed entity.